ANALISIS LINGKUNGAN KERJA DAN JOB INSECURITY TERHADAP TURNOVER INTENTION DENGAN WORK LIFE BALANCE SEBAGAI VARIABEL MODERATING PADA PT. KERETA API INDONESIA STASIUN BESAR RANTAUPRAPAT - Hazrulta Aulia; Pristiyono Pristiyono; Rizki Syahputra; Zuriani Zuriani; Desmawati Hasibuan (LP2M Universitas Bina Bangsa, 2021)
This study aims to answer the influence of work environment and work insecurity on turnover intention with work life balance as a moderation variable in PT. Rantauprapat Railway. Data collection was conducted by distributing questionnaires to employees of PT KAI Rantauprapat numbering 75 people. This research uses quantitative method and perform data processing with IBM SPSS Statistic 20 tools. This analysis includes reliability test, validity test, classic assumption test, statistical test, multiple linear regression test and moderation test using Moderated Regression Analysis (MRA). The result of the t (partial) test showed that the work environment had a positive and significant effect on turnover intentions with a coefficient value of 0.644 with a probability value of 0.000 and a calculated t value of 6.535. Job insecurity has a positive and significant effect on turnover intention with a coefficient value of 0.259 with a probability value of 0.045 and a calculated t value of 2.043. While the results of the f test (simultaneous) showed a value of 27,286 which means that the work environment and work insecurity together have a significant effect on turnover intention. Multiple linear test results showed a yield of Y = 3.961 + 0.644 X1 + 0.259X2. Work life balance cannot moderate the influence of the work environment and work insecurity on turnover intention.